Psychiatric Aspects of Childhood Epilepsy - PATTANAYAK, Raman Deep; SAGAR, Rajesh (Iranian Journal of Child Neurology, 2012)
How to Cite this Article: Pattanayak RD, Sagar R. Psychiatric Aspects of Childhood Epilepsy. Iran J Child Neurol 2012;6(2):9-18. Childhood epilepsy is a chronic, recurrent disorder of unprovoked seizures. Theonset of epilepsy in childhood has significant implications for brain growth anddevelopment. Seizures may impair the ongoing neurodevelopmental processes and compromise the child’s intellectual and cognitive functioning, leading totremendous cognitive, behavioral and psychosocial consequences. Children with epilepsy are at increased risk for emotional and behavioral problems. In addition to the direct effects of epilepsy, there are multiple contributory factors including the underlying neurological abnormalities and adverse effects of medication. This review discusses the current understanding of various psychiatric aspects of childhood epilepsy, including the neuropsychological, behavioral and psychosocial concomitants of childhood epilepsy. References 1. Shinnar S, Pellock JM. Update on the epidemiology and prognosis of pediatric epilepsy. J Child Neurol 2002;7 suppl 1:4-17. 2. Murphy CC, Trevathan E, Yeargin-Allsopp M. Prevalence of epilepsy and epileptic seizures in 10-year-old children: results from the Metropolitan Atlanta Developmental Disabilities Study. Epilepsia 1995;36(9):866-72. 3. Placencia M, Shorvon SD, Paredes V, Bimos C, Sander JW, Suarez J, et al. Epileptic seizures in an Andean region of Ecuador ncidence and prevalence and regional variation. Brain 1992;115:771-82. 4. Henkin Y, Sadeh M, Kivity S, Shabtai E, KishonRabin L, Gadoth N. Cognitive function in idiopathic generalized epilepsy of childhood. Dev Med Child Neurol 2005;47:126-32. 5. Rodenburg R, Stams GJ, Meijer AM, Aldenkamp AP, Dekovic M. Psychopathology in children with epilepsy: a meta-analysis. J Pediatr Psychol 2005;30(6):453-68. 6. Caplan R, Siddarth P, Gurbani S, Ott D, Sankar R, Shields WD. Psychopathology and pediatric complex partial seizures: seizure-related, cognitive, and linguistic variables. Epilepsia 2005;45:273-81. 7. International League Against Epilepsy- Epidemiology commission. Available from: URL: http://www.ilaeepilepsy.org/. Accessed September 1, 2011. 8. Eriksson KJ, Koivikko MJ. Prevalence, classification and severity of epilepsy and epileptic syndromes in children. Epilepsia 1997;38:1275-82. 9. Sillanpaa M, Jalava M, Kaleva O, Shinnar S. Long-term prognosis of seizures with onset in childhood. N Engl J Med 1998;338(24):1715-22. 10. Berg AT, Shinnar S, Levy SR Testa FM, Smith-Rapaport S, Beckerman B. Early development of intractable epilepsy in children: a prospective study. Neurology 2001;56:1445-52. 11. Rutter M, Graham P, Yule W. A neuropsychiatric study in childhood. Clinics in developmental medicine no 35/36.Philadelphia: JB Lippincott; 1970.P.175-85. 12. Solomon, GE, Pfeffer C. Neurobehavioral abnormalities in epilepsy. In: Frank Y, editor. Pediatric behavioral epilepsy: New York: CRC press; 1996. P. 269-87. 13. Farwell JR, Dodrill CB, Batzel LW. Neuropsychological abilities of children with epilepsy. Epilepsia 1985;26:395-400. 14. Nolan MA, Redoblado MA, Lah S, Sabaz M, Lawson JA, Cunningham AM, et al. Intelligence in childhood epilepsy syndromes. Epilepsy Res 2003;53:139-50. 15. Berg AT, Langfitt JT, Testa FM, Levy SR, DiMario F, Westerveld M, et al. Residual cognitive effects of uncomplicated idiopathic and cryptogenic epilepsy. Epilepsy Behav 2008;13:614-9. 16. van Mil SG, Reijs RP, van Hall MH, Aldenkamp AP. Neuropsychological profile of children with cryptogenic localization related epilepsy. Child Neuropsychol 2008;14:291-302. 17.Williams J, Griebel ML, Dykman RA. Neuropsychological patterns in pediatric epilepsy. Seizure 1998;7:223-8. 18. Goodman R. Brain disorders. In: Rutter M, Taylor EA, editors. Child and adolescent psychiatry, 4th edition. Oxford: Blackwell Scientific Publications; 2002. P. 241-60. 19. Elger CE, Helmstaedter C, Kurthen M. Chronic epilepsy and cognition. Lancet Neurol 2004;3(11):663-72. 20. Bujoreanu, IS, Ibeziako P, DeMaso DR. Psychiatric concerns in pediatric epilepsy. Child Adolesc Psychiatr Clin N Am 2010;19(2):371-86. 21. Hermann BP, Lin, JJ, Jones, JE, Seidenberg S. The emerging architecture of neuropsychological impairment in epilepsy. Neurol Clin 2009;27(4):881-907. 22. Hermann B, Seidenberg M, Bell B, Rutecki P, Sheth R, Ruggles K, et al. The neurodevelopmental impact of childhood-onset temporal lobe epilepsy on brain structure and function. Epilepsia 2002;43(9):1062-71. 23. Loring DW, Meador KJ. Cognitive side effects of antiepileptic drugs in children. Neurology 2004;62(6):872-7. 24. McDermott S, Mani S, Krishnaswami S. A populationbased analysis of specific behavior problems associated with childhood seizures. J Epilepsy 1995;8:110-8. 25. Davies S, Heyman I, Goodman, R. A population survey of mental health problems in children with epilepsy. Dev Med Child Neurol 2003;45(5):292-5. 26. Kaufmann R, Goldberg-Stern H, Shuper A. Attentiondeficit disorders and epilepsy in childhood: incidence, causative relations and treatment possibilities. J Child Neurol 2009;24(6):727-33. 27. Buelow JM, Austin JK, Perkins SM, Shen J, Dunn DW, Fastenau PS. Behavior and mental health problems in children with epilepsy and low IQ. Dev Med Child Neurol 2003;45(10):683-92. 28.Williams J, Lange B, Phillips T, Sharp GB, DelosReyes E, Bates S, et al. The course of inattentive and hyperactiveimpulsive symptoms in children with new onset seizures. Epilepsy Behav 2002;3(6):517-21. 29. Hermann B, Seidenberg M, Jones J. The neurobehavioural comorbidities of epilepsy: can a natural history be developed? Lancet Neurol 2008;7(2):151-60. 30. Schoenfeld J, Seidenberg M, Woodard A, Hecox K, Inglese C, Mack K, et al. Neuropsychological and behavioral status of children with complex partial seizures. Dev Med Child Neurol 1999;41(11):724-31. 31. Austin JK, Caplan R. Behavioral and psychiatric comorbidities in pediatric epilepsy: toward an integrative model. Epilepsia 2007;48(9):1639-51. 32. Ott D, Caplan R, Guthrie D, Siddarth P, Komo S, Shields WD, et al. Measures of psychopathology in children with complex partial seizures and primary generalized epilepsy with absence. J Am Acad Child Adolesc Psychiatry 2001;40(8):907-14. 33. Mathiak KA, Luba M, Mathiak, K, Karzel, K, Wolanczyk, Szczepanik E, et al. Quality of life in childhood epilepsy with lateralized epileptogenic foci. BMC Neurol 2010;10:69. 34. Bulteau C, Jambaque I, Viguier D, Kieffer V, Dellatolas G, Dulac O. Epileptic syndromes, cognitive assessment and school placement: a study of 251 children. Dev Med Child Neurol 2000;42(5):319-27. 35.Noeker M, Haverkamp F. Neuropsychological deficiencies as a mediator between CNS dysfunction and inattentive behaviour in childhood epilepsy. Dev Med Child Neurol 2003;45(10):717-8. 36. Sillanpää M, Helen Cross J. The psychosocial impact of epilepsy in childhood. Epilepsy Behav 2009;15 Suppl 1:S5-10. 37. Miller V, Palermo TM, Grewe SD. Quality of life in pediatric epilepsy: Demographic and disease-related predictors and comparison with healthy controls. Epilepsy Behav 2003,4(1):36-42. 38. Kokkonen J, Kokkonen ER, Saukkonen AL, Pennanen P. Psychosocial outcome of young adults with epilepsy in childhood. J Neurol Neurosurg Psychiatry 1997;62(3):265-8. 39. Pal DK, Chaudhury G, Sengupta S, Das T: Social integration of children with epilepsy in rural India. Soc Sci Med 2002;54(12):1867-74. 40. Modi AC. The impact of a new pediatric epilepsy diagnosis on parents: parenting stress and activity patterns. Epilepsy Behav 2009;14(1):237-42. 41. Shore C, Austin J, Musick B, Dunn D, McBride A, Creasy K. Psychosocial care needs of parents of children with new-onset seizures. J Neurosci Nurs 1998;30:169-74. 42. Rodenburg R, Marie Meijer A, Dekovic´ M, Aldenkamp AP. Family predictors of psychopathology in children with epilepsy. Epilepsia 2006;47(3):601-14. 43.Mims J. Self-esteem, behavior, and concerns surrounding epilepsy in siblings of children with epilepsy. J Child Neurol 1997;12(3):187-92. 44. Pavlou E, Gkampeta A. Learning disorders in children with epilepsy. Childs Nerv Sys 2011;27(3):373-9. 45. Fastenau PS, Shen J, Dunn DW, Perkins SM, Hermann BP, Austin JK. Neuropsychological predictors of academic underachievement in pediatric epilepsy: moderating roles of demographic, seizure, and psychosocial variables. Epilepsia 2004;45(10):1261-72. 46. Austin JK, Caplan R. Behavioral and psychiatric comorbidities in pediatric epilepsy: toward an integrative model. Epilepsia 2007;48(9):1639-51. 47. Austin JK, McNelis AM, Shore CP, Dunn DW, Musick B. A feasibility study of a family seizure management program ‘Be seizure smart’. J Neurosci Nurs 2002;34:30-7. 48. Ronen GM, Streiner DL, Rosenbaum P. Health-related quality of life in childhood epilepsy: Moving beyond ‘seizure control with minimal adverse effects’. Health Qual Life Outcomes 2003;1:36. 49. Smith K, Siddarth P, Zima B, Sankar R, Mitchell W Gowrinathan R, et al. Unmet mental health needs in pediatric epilepsy: insights from providers. Epilepsy Behav 2007;11(3):401-8. 50. Goldstein J, Plioplys S, Zelko F, Mass S, Corns C, Blaufuss R, et al. Multidisciplinary approach to childhood epilepsy: exploring the scientific rationale and practical aspects of implementation. J Child Neurol 2004;19(5):362-78. 51. Achenbach TM. Manual for the child behavior checklist/4-18 and 1991 profile. Burlington, VT: Univ. of Vermont Department of Psychiatry; 1991. 52. Gadow KD, Sprafkin J. Child symptom inventory-4 norms manual. Stony Brook, NY: Checkmate Plus; 1997. 53. Sabaz M, Cairns DR, Lawson JA, Nheu N, Bleasel AF, Bye AM. Validation of a new quality of life scale for children with epilepsy. Epilepsia 2000;41(6):765-74. 54. Camfield C, Breau L, Camfield P. Impact of pediatric epilepsy on the family: a new scale for clinical and research use. Epilepsia 2001;42(1):104-12. 55. Lewis MA, Salas I, de la Sota A, Chiofalo N, Leake B. Randomized trial of a program to enhance the competencies of children with epilepsy. Epilepsia 1990;31(1):101-9. 56. Ziegler RG, Erba G, Holden L, Dennison H. The coordinated psychosocial and neurologic care of children with seizures and their families. Epilepsia 2000;41(6):732-43. 57.Wagner JL, Smith G. Psychosocial intervention in pediatric epilepsy: a critique of the literature. Epilepsy Behav 2006;8(1):39-49. 58. Macrodimitris S, Sherman EM, Forde S, Tellez-Zenteno JF, Metcalfe A, Hernandez-Ronquillo L, et al. Psychiatric outcomes of epilepsy surgery: a systematic review. Epilepsia 2011;52(5):880-90. 59. Chin RF, Cumberland PM, Pujar SS, Peckham C, Ross EM, Scott RC. Outcomes of childhood epilepsy years at age 33 years: a population-based birth-cohort study. Epilepsia 2011;52(8):1513-21.